Perilaku Wanita Pekerja Seksual tidak Langsung (Pendamping Lagu) dalam Pencegahan AIDS di Kabupaten Pekalongan - Bayu Agung Pribadi; Rr. Vita Nur Latif; Nur Hilal; Elsye Rumemper (Pena Medika Jurnal Kesehatan, 2011)
Background & Methode : Indirect female sexual workers who is operate as such as camouflaged as sex commercial, usually she works on special work and the side jobs is sexual workers. The subject research is a singer or back sound in song room (karaoke). They are kind of group who have high risk to influence HIV & AIDS case. The Purpose of this research is to describe the attitude of indirect sex worker, especiallywho have main profession as a back sound to preventions AIDS in Pekalongan Regency.This Research is designed exploratory research with cross sectional approach, research of qualitative method. The informan include five indirect female sexual workers  in several research locations.Result : Result for this research showed part of indirect sex worker done know how to prevented HIV & AIDS used condoms, their practice to AIDS’s prevention effort still less. Although they agree to use condom as a good preventions systems. In their perceptions, condoms just only to avoid pregnancy, not for avoid PMS or HIV/AIDS transmitions. Recommendation for health department, more increase collaboration with sectoral link especially academic sector to decrease HIV/AIDS especially in this community.Keywords : Indirect female sexual workers, behavior to prevented HIV/AIDS.